A comparison of the effectiveness of cyclophosphamide, leflunomide, corticosteroids, or conservative management alone in patients with IgA nephropathy: a retrospective observational study - Chen, Shasha (Sci Rep, 2018)
To compare the long-term efficacy of corticosteroids (P) alone or in combination with cyclophosphamide (CTX), leflunomide (LEF), or Angiotensin-convertase inhibitors or angiotensin II receptor blockers (ACEI/ARB) in treatment for IgA nephropathy (IgAN), 311 patients with IgAN were identified. Therapeutic effectiveness (including progression, partial remission, complete remission) and combined renal endpoint (defined as 30% reduction in eGFR or ESRD) were compared based on different therapies. After immunosuppressive and ACEI/ARB treatment, the levels of eGFR, proteinuria and albumin were significantly improved at the last follow-up, the extent of improvement of eGFR, proteinuria, and albumin was more notable in P + CTX group and P + LEF group. 41%, 52.2%, 55.3% and 55.2% in P + CTX, P + LEF, P and ACEI/ARB group achieved complete remission, respectively. Multivariate regression analysis indicated that only proteinuria (Relative risk (RR) 0.82(0.72–0.94), P = 0.004) and tubular atrophy/interstitial fibrosis (RR 0.26(0.13–0.57), P = 0.001) were predictors for complete remission. The optimal cutoffs of eGFR was 47.085 ml/min/1.73 m(2) predicting renal function recovery in P + CTX therapy. In conclusion, tubular atrophy/interstitial fibrosis and massive proteinuria were poor predictors for complete remission in IgAN, it appears as though patients may have benefited from immunosuppressive treatment but that comparison to a well-matched contemporary control group or, ideally, a randomized controlled clinical trial, would be required to show this.